Modeling Conflict Resolution in Ethiopian Social Networks (2015–2025): A Statistical Physics Approach to Stability and Equilibrium Dynamics - Belay Sitotaw Goshu; Muhammad Ridwan (Polit Journal Scientific Journal of Politics, 2025)
Ethiopia’s social networks from 2015 to 2025 have been marked by ethnic tensions and conflict, necessitating strategies to enhance stability and cohesion. This study aims to identify key factors influencing stability in Ethiopian social networks and propose data-driven strategies for conflict resolution. A small-world network with 100 nodes was simulated using the Ising model at (T = 0.5), with sensitivity analysis varying rewiring probabilities (p = 0.05, 0.1, 0.2) and external influence (h = 0.0, 0.1, 0.3) over 5000 iterations. Simulated empirical data included influence scores and edge weights, reflecting real-world dynamics. High clustering (0.45 at (p = 0.05) correlated with stability, while high (h) (0.3) reduced stability by 12%. Clustering-magnetization correlations ranged from 0.8016 (h = 0.0) to -0.9665 (h = 0.3), and betweenness-magnetization correlations shifted from 0.4639 to -0.7603, highlighting external influence’s disruptive effect. Clustering drives stability, but excessive external influence undermines it, as seen in Ethiopia’s conflict patterns. Policymakers should strengthen local networks and minimize external interventions to enhance cohesion.